The Effect of Village Income and Gross Regional Domestic Product on Poverty in Indonesia - Aji, Yore Isti Tosan (Research and Development Agency Ministry of Home Affairs, 2022)
The problem of poverty still exists today, and economic disparities are still found in districts/cities in Indonesia. The government has taken various ways to alleviate the problem of poverty, one of which is by distributing village funds to all corners of the country. Based on the data availability in Buku Saku Dana Desa and Buku Pintar Dana Desa published by the Ministry of Finance, Village income from 2015 to 2017 tends to increase. Meanwhile, the number of poor individuals throughout Indonesia between 2016 and 2017 has decreased. This paper attempts to examine whether or not Village Income, such as Village Funds, Revenue Sharing Taxes and Levies, Village Fund Allocations, and Village Original Income, as well as the GRDP (Gross Regional Domestic Product), affect the incidence of District/City poverty in Indonesia. This study uses secondary data from Statistics Indonesia for two years, consisting of 407 districts/cities in Indonesia each year. The regression analysis with static panel data using a double log model is the data analysis technique used in this article. The results show that Village Income and GRDP have an effect on poverty in districts/cities in Indonesia, with values of -0.0004 for Village Funds, 0.003 for Revenue Sharing Taxes and Levies, -0.026 for Village Fund Allocation, 0.002 for Village Original Income, and -0.197 for Gross Regional Domestic Product. We advise the government to increase village fund transfers, village fund allocation, and GRDP to lower poverty levels.